Valproate-induced reactive lymphoid hyperplasia in pediatric population: A rare case report - Kanwardeep Kaur,; Mohanvir Kaur,; Sanya Jain, (Indian Journal of Case Reports, 2021)
Certain drugs may give rise to lymph node enlargement, predominantly in the neck known as drug-induced lymphadenopathy which may be associated with the involvement of DRESS syndrome (Drug Reaction with Eosinophilia and Systemic Symptoms) of drug reaction with eosinophilia and systemic symptoms also known as drug-induced hypersensitivity syndrome. It can also resemble lymphoma morphologically and this condition is known as pseudolymphoma. Valproate, a broad-spectrum antiepileptic, also used in bipolar disorders and migraine prophylaxis, is generally well tolerated. To date, very few cases of valproate monotherapy-induced lymphoid hyperplasia have been reported worldwide. Here, we are reporting one such rare case in a 13-year-old Indian male child who developed cervical lymphoid hyperplasia following the use of sodium valproate for 5 months for a seizure disorder.